Dispersal and Deposition of Detritus From Kelp Cultivation - Broch, Ole Jacob; Hancke, Kasper; Ellingsen, Ingrid Helene (Frontiers in Marine Science, 2022)
A high resolution coastal and ocean hydrodynamic model system was used to investigate the transport and deposition patterns of Particulate Organic Matter (POM) from kelp farmed at three locations of different properties: a sheltered location, an exposed location, and an offshore location. Published values on the sinking speeds of organic particles from kelp were used, spanning several orders of magnitude. Recent work on quantifying the release of particulate organic matter from farmed kelp was used to link the release of carbon to possible cultivation volumes and scenarios, and finally to link this to the potential for carbon loading on the ocean floor. The results are presented in terms of loading and distribution per unit harvested kelp, and the loading estimates are compared with estimates of natural (background) primary production. According to the simulation results, organic matter may be transported anything from a few (hundred) meters up to a hundred km away from the release site, depending on the sinking rates, time of release, and the location. The depth at which the matter settles on the sea floor likewise depends on the properties of the matter and the sites. The time until settlement varied from minutes to several hundred hours. The results underscore the importance of constraining the dispersal and deposition of detritus from kelp cultivation in order to better understand and quantify associated environmental risks posed by organic loading, and the potential for seafloor carbon sequestration by kelp farming as a nature based climate solution.